Outcomes of Salvage Procedures for Failed Total Ankle Arthroplasty. (April 2023) - Pfahl, Kathrin; Röser, Anke; Eder, Julia; Gottschalk, Oliver; Hörterer, Hubert; Mehlhorn, Alexander; Walther, Markus
Background: The number of total ankle arthroplasty (TAA) procedures increased rapidly in the last years and so have its complications. The main pillars in treating failed TAA are revision total ankle arthroplasty (RTAA), revision total ankle arthrodesis (RAA), or revision tibiotalocalcaneal fusion (RTTC). To evaluate these options, we compared clinical, radiologic, and patient-reported outcomes. Methods: A single-center, retrospective review of 111 cases of revision procedures of failed TAA from 2006 to 2020 was performed. Patients undergoing polyethylene exchange and revision of one metallic component were excluded. Demographic data, failure, and survival rates were analyzed. The European Foot and Ankle Society (EFAS) score and radiographic changes in the subtalar joint were evaluated. The average follow-up was 67.89 ± 40.51 months. Results: One hundred eleven patients underwent removal of TAA. The procedures included 40 revisions of both metallic components, 46 revision total ankle arthrodesis and 25 revision tibiotalocalcaneal fusion. The overall failure rate in the cohort was 5.41% (6/111). The failure rate after RAA was 4.35 times higher than that of RTAA, whereas RTTC did not show failures. RTAA and RTTC lead to a 1-year and 5-year survival rate of 100%. RAA resulted in a 1-year survival rate of 90% and a 5-year survival rate of 85%. The mean EFAS score in the cohort was 12.02 ± 5.83. Analysis of the EFAS score showed that RTTC provided the most reliable pain reduction, and RTAA achieved the best gait pattern. RAA resulted in poorer clinical results. Subtalar joint degeneration occurred significantly less in the RTAA group ( P  = .01). Conclusion: This retrospective study suggests lower failure rates, increased short-term survival and a better clinical outcomes of revision arthroplasty and tibiotalocalcaneal fusion than ankle arthrodesis. Revision arthroplasty is a promising solution in treating failed total ankle arthroplasty considering lower rate of subsequent adjacent joint degeneration. Level of Evidence: Level III, non-randomized observational study.